2016
DOI: 10.1007/s11746-016-2864-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Seeds From Wild and Cultivated Ginseng (Panax ginseng Meyer): Occurrence of a High Level of Petroselinic Acid

Abstract: medicine for thousands of years. In the Russian Far East, ginseng grows naturally in taiga forests and is enlisted in the Red Data Book of the Russian Federation. In many countries, ginseng is cultivated as a medicinal plant. Recent pharmacological investigations confirm the healing effects of ginseng on human health, which are associated mainly with the action of glycosides (ginsenosides) localized in roots [1]. Furthermore, many other numerous compounds such as phytosterols, polyphenols, polyacetylenes, alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ginseng seeds are used to cultivate ginseng and recent studies have shown that ginseng seeds contain biologically active compounds similar to those in ginseng roots [ 18 ]. Ginseng seeds contain functional compounds, such as fatty acids [ 19 ], phytosterols [ 20 ], and saponins [ 18 ]. These compounds in the ginseng seeds have been reported to prevent skin aging [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng seeds are used to cultivate ginseng and recent studies have shown that ginseng seeds contain biologically active compounds similar to those in ginseng roots [ 18 ]. Ginseng seeds contain functional compounds, such as fatty acids [ 19 ], phytosterols [ 20 ], and saponins [ 18 ]. These compounds in the ginseng seeds have been reported to prevent skin aging [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%